1979
DOI: 10.1159/000137234
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Cardiotoxic Effects of Ouabain by Acepromazine, Tetrodotoxin and Magnesium Sulphate

Abstract: Acepromazine (500 μg), tetrodotoxin (0.5 μg) and magnesium sulphate (7.5 mg twice) given intracerebroventricularly increased the doses of ouabain given by continuous intravenous infusion, required to induce arrhythmias and death. Acepromazine (150 μg kg–1) was also effective when administered intravenously. Acepromazine (1.5 mg kg–1) and tetrodotoxin (4-6μg kg–1) given intravenously did not protect against, and even increased, the toxicity of ouabain. Both substances decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The doses of ouabain required to cause maximal chemoreceptor discharge are shown in Table 1. Comparing these doses with those needed to cause ventricular extrasystoles when administered by the intracarotid route (64 + 5 jug/kg, n = 3) or intravenously (69 ± 2,ug/kg, n = 6: Peres-Gomes & Ribeiro, 1979) showed that with intracarotid ouabain a significant difference (P < 0 05) exists between chemoreceptor activation and cardiotoxic doses, whereas little or no difference is apparent between chemoreceptor activation and cardiotoxic effect when ouabain is administered intravenously.…”
Section: Cardiotoxic Actions Of Ouabainmentioning
confidence: 99%
“…The doses of ouabain required to cause maximal chemoreceptor discharge are shown in Table 1. Comparing these doses with those needed to cause ventricular extrasystoles when administered by the intracarotid route (64 + 5 jug/kg, n = 3) or intravenously (69 ± 2,ug/kg, n = 6: Peres-Gomes & Ribeiro, 1979) showed that with intracarotid ouabain a significant difference (P < 0 05) exists between chemoreceptor activation and cardiotoxic doses, whereas little or no difference is apparent between chemoreceptor activation and cardiotoxic effect when ouabain is administered intravenously.…”
Section: Cardiotoxic Actions Of Ouabainmentioning
confidence: 99%
“…The interaction between these membrane proteins could have consequences for the function of Atelopus toxin cocktails. Interestingly, tetrodotoxin reduces the toxicity of cardiac glycosides (CGs) when injected directly into the brain of cats but potentiates CG toxicity when given intravenously ( Peres-Gomes and Ribeiro, 1979 ). The difference in effect between TTX administered to the brain and TTX administered intravenously is probably a consequence of the impermeability of the blood-brain barrier to TTX ( Zimmer, 2010 ).…”
Section: Atelopus Chemical Defense Characteristics: Ecologic...mentioning
confidence: 99%